Comparison of three common nutritional screening tools with the new European Society for Clinical Nutrition and Metabolism (ESPEN) criteria for malnutrition among patients with geriatric gastrointestinal cancer: a prospective study in China - Ye, Xiao-Jun; Ji, Yan-Bin; Ma, Bing-Wei; Huang, Dong-Dong; Chen, Wei-Zhe; Pan, Zong-You; Shen, Xian; Zhuang, Cheng-Le; Yu, Zhen (BMJ open, 2018)
ObjectiveThe aim of this study was to evaluate and compare three common nutritional screening tools with the new European Society for Clinical Nutrition and Metabolism (ESPEN) diagnostic criteria for malnutrition among elderly patients with gastrointestinal cancer.Research methodsandproceduresNutritional screening tools, including the Nutritional Risk Screening 2002 (NRS 2002), the Malnutrition Universal Screening Tool (MUST) and the Short Form of Mini Nutritional Assessment (MNA-SF), were applied to 255 patients with gastrointestinal cancer. We compared the diagnostic values of these tools for malnutrition, using the new ESPEN diagnostic criteria for malnutrition as the ‘gold standards’.ResultsAccording to the new ESPEN diagnostic criteria for malnutrition, 20% of the patients were diagnosed as malnourished. With the use of NRS 2002, 52.2% of the patients were found to be at high risk of malnutrition; with the use of MUST, 37.6% of the patients were found to be at moderate/high risk of malnutrition; and according to MNA-SF, 47.8% of the patients were found to be at nutritional risk. MUST was best correlated with the ESPEN diagnostic criteria (К=0.530, p<0.001) compared with NRS 2002 (К=0.312, p<0.001) and MNA-SF (К=0.380, p<0.001). The receiver operating characteristic curve of MUST had the highest area under the curve (AUC) compared with NRS 2002 and MNA-SF.ConclusionsAmong the tools, MUST was found to perform the best in identifyingmalnourished elderly patients with gastrointestinal cancer distinguished by the new ESPEN diagnostic criteria for malnutrition. Nevertheless, further studies are needed to verify our findings.Trial registration numberChiCTR-RRC-16009831; Pre-results.